تحديات نظام الأمن الجماعي للأمم المتحدة - محدة, عبد الباسط (revue mofakir; No 12 (2015): مجلـــة المفكــر, 2018)
This paper aims to discuss the notion and application of collective security. This work problematizes the idea of collective security by interrogating the challenges that its application presents and the unevaluated successes that its proponents credit to it. The concept of collective security has been credited with averting likely wars, but has remained insufficient attempting to contribute to international peace and justice. Its application is increasingly paralyzed by the increasing resort to unilateral action by powerful nations, the persistent problem of double standards pursued by international political and judicial organizations, and lack of a real sense of oneness of the international community. As globalization takes centre stage as a result of the ever increasing interactions and technological advancements, the current collective security system still lags behind, incapable of handling the existing and future global challenges to peace and security. Hence, changing the traditional competitive, and at times, aggressive behavior of nations towards each other, changing the way poor nations perceive and interact with international political and judicial organizations, and introducing radical measures to reform the UN security council are but some of the recommendations that this paper fronts as central to meaningful collective security in principle and application.